2021
DOI: 10.2340/00015555-3802
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the PsoWell™ Model for the Management of People with Complex Psoriasis

Abstract: The Psoriasis and Well-being (PsoWell)™ training programme, incorporating motivational interviewing, improves clinicians’ knowledge and skills to manage complex psoriasis, including behaviour change. The aims of this study were to deliver the PsoWell™ training programme to dermatology specialists, and to evaluate the acceptability and feasibility of implementing the PsoWell™ model across dermatology services. Framework analysis of 19 qualitative semi-structured interviews was performed, following delivery of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…Improving clinicians’ awareness of how their personal models impact on psoriasis management and their relationships with patients may improve patient outcomes, such as increased adherence. PsoWell™ (psoriasis and wellbeing) is an evidence‐based training programme that specifically aims to teach health professionals who are involved in psoriasis management motivational interviewing 30 techniques to promote better patient self‐management and increase shared decision making within a consultation 11,31 . Attending the PsoWell™ training programme could help clinicians to become more aware of their personal models of psoriasis and improve their consultation skills.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Improving clinicians’ awareness of how their personal models impact on psoriasis management and their relationships with patients may improve patient outcomes, such as increased adherence. PsoWell™ (psoriasis and wellbeing) is an evidence‐based training programme that specifically aims to teach health professionals who are involved in psoriasis management motivational interviewing 30 techniques to promote better patient self‐management and increase shared decision making within a consultation 11,31 . Attending the PsoWell™ training programme could help clinicians to become more aware of their personal models of psoriasis and improve their consultation skills.…”
Section: Discussionmentioning
confidence: 99%
“…PsoWell TM (psoriasis and wellbeing) is an evidencebased training programme that specifically aims to teach health professionals who are involved in psoriasis management motivational interviewing 30 techniques to promote better patient self-management and increase shared decision making within a consultation. 11,31 Attending the PsoWell TM training programme could help clinicians to become more aware of their personal models of psoriasis and improve their consultation skills. Our findings also suggest that as female clinicians are more likely to involve patients in treatment decisions, the PsoWell TM training programme may be an ideal professional development activity for male clinicians, in particular, who are interested in facilitating shared decision making in their practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hewitt and colleagues (2021) examined the effects of a motivational interview and one-day training for professionals in the United Kingdom to help change behavior in psoriasis patients. Representatives of several professions, dermatologists, psychologists, and nurses also participated in the training, and it was reported that this increased their skills, confidence, and motivation to support their patients' behavioral changes (Hewitt et al, 2021). Psychodermatology seminars were held in the city of Kiel, Germany between 2018 and 2020 as part of an educational program for medical students from the University Department of Dermatology, during which students had the opportunity to learn about skin stress and the biopsychosocial disease model (Wittbecker et al, 2021).…”
Section: Challenges and Development Opportunities In Psychodermatologymentioning
confidence: 99%